A Correlation Between Oral Reading Fluency And Reading Comprehension At Tenth Grade Students MAS TI Canduang - Molina Miranda; Reflinda (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2022)
The researcher wanted to investigate the correlation between oral reading fluency and reading comprehension at the tenth grade of MAS TI Canduang academic years 2019/2020. The design of this research was correlation research. Then, the instruments that used in this research were oral test for measuring oral reading fluency and written test for measuring reading comprehension. The population of this research was all of the tenth grade students of MAS TI Canduang in the academic year of 2019/2020 which consists of 5 classes. The sample was 40 students taken by simple random sampling technique. The results of this research show that there is a correlation between oral reading fluency and reading comprehension at the tenth grade of MAS TI Canduang in academic years 2019/2020. The researcher found that the coefficient of correlation between oral reading fluency and reading comprehension at the tenth grade of MAS TI Canduang was 0,47. The correlation was positive and significant. It means that Ho is rejected. In short, there is a positive correlation between oral reading fluency and reading comprehension at the tenth grade of MAS TI Canduang. Related to the result of the research, it can be concluded that oral reading fluency has positive contribution in reading comprehension. The notion is the more fluent oral reader, the more proficient she/he is in reading comprehension. In summary, this research is conducted for finding the correlation between oral reading fluency and reading comprehension at the tenth grade of MAS TI Canduang.